Flora of Ceará, Brazil: Portulacaceae s.s. - Loiola,Maria Iracema Bezerra (2022)
Abstract This study aimed to carry out a floristic inventory and update the geographical distribution of Portulacaceae species that occur in the state of Ceará, Northeast Region of Brazil. The field expeditions for collection and observation of species were realized between March/2015 and March/2021. Six species of Portulaca have been recorded in the state of Ceará, being identified mainly by habit, margin and leaf shape, flower coloration, operculum shape, and seed ornamentation. All species occur in Conservation Units in the state of Ceará: P. elatior, P. halimoides, P. mucronata, P. oleracea, P. pilosa and P. umbraticola. The highest floristic richness was found in the Stepic Savanna, where all species were recorded. Portulaca halimoides had the widest distribution in Ceará, with 17 records, occurring in various vegetation types, especially in the Stepic Savanna. Portulaca mucronata was registered exclusively in Stepic Savanna, being the species with the lowest number of records. Identification key, descriptions, comments about the species, taxonomic relationships, phenological data and photographs of the species are presented here.